Identification Of Trichuris Trichiura Worms Eggs in 6-8 Years Old Elementary School Children At GKPS Private Elementary School, Saribudolok, Simalikuta, Simalungun - rajagukguk, Tiara; Aritonang, Erlan (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Tricuriasis is an infection caused by the eggs of the Trichuris trichiura worm which is often found in humans, can show symptoms such as diarrhea, anemia, lack of protein energy, weight loss and accompanied by headaches and fever. Trichuris trichiura is an intestinal nematode worm habitat in the human digestive tract, including a group of worms that are transmitted through soil (Soil Transmitted Helmints). Research has been carried out at the Chemistry-Biology Laboratory, Sari Mutiara University. This study aims to identify Trichuris trichiura worm eggs in the feces of elementary school children aged 6-8 years at SD Swata GKPS Saribudolok City, Silimakuta District, Simalungun Regency in 2022.